PENGARUH INFLASI DAN INVESTASI TERHADAP NILAI TUKAR RUPIAH - Istiqomah Istiqomah (Signifikan: Jurnal Ilmu Ekonomi, 2013)
Exchange rate is defined as a currency that can be exchange per unit to another currency, or the price of one currency to another currency. The purpose of this research is to know the effect of Inflation and investment to rupiah`s exchange rate in Indonesia. Variable which is used in this research is rupiah`s Exchange Rate to US dollar`s (ER), Inflation, Domestic Direct Investment (DDI), Foreign Direct Investment (FDI), and also Dummy crisis variable (DM) of Indonesia. The sources of the data are from Central Bank of Indonesia and Indonesia Statistical Base. OLS (Ordinary Least Square) method was used for analyzing in Eviews 5.1 program. The results of this research is to indicate inflation, foreign direct investment and dummy crisis that gave the positive influence to the rupiah`s exchange rate in Indonesia significantly. Meanwhile, domestic direct investment has not positive influence to the rupiah’s exchange rate in Indonesia significantlyDOI: 10.15408/sjie.v2i1.2373